Plant-parasitic Nematodes Associated with Grasses Grown for Seed in the Willamette Valley of Oregon - Rivedal H. M.; Zasada I. A.; Temple T. N.; Peetz A. B.; Núñez-Rodríguez L. A.; Starchvick R. J.; Braithwaite E. T. (Journal of Nematology)
Plant-parasitic nematodes (PPN) are an understudied pathogen group in the Oregon cool-season grass seed cropping system. In this survey, the PPN associated with annual ryegrass, bentgrass, fine fescue, orchardgrass, perennial ryegrass, and tall fescue were determined. Thirty-seven fields were sampled in the 2022 or 2023 growing season by collecting 10 soil cores in each of six 100-m transects for nematode extraction and visual identification. PerMANOVA testing indicated significant differences in PPN community composition across grass host and sampling time. Pratylenchus and Meloidogyne were the most commonly encountered nematodes, with maximum population densities of 1,984 and 2,496 nematodes/100 g soil, respectively. Sequencing of the COX1 gene region indicated the presence of P. crenatus, P. fallax, P. neglectus, P. penetrans, and P. thornei, with some of these species being detected for the first time on these grass hosts. The only Meloidogyne sp. found in these grasses was M. nassi, based upon sequencing of the ITS gene region. This first-of-its-kind survey indicates the need for further assessment of the impact of these PPNs on yield and stand longevity in cool-season grass seed fields in Oregon.